EXAMINATION INDICES OF THE STATE OF THE VEGETATIVE NERVOUS SYSTEM IN CASE OF PERIODONTAL DISEASES IN THE PATIENTS WITH AFFECTED CERVICAL INTERVERTEBRAL DISCS - V. M. Kulygina; T.O. Tepla (Український стоматологічний альманах)
Rationale of the topic. There is a certain stable dependence between the state of periodontal tissues and general somatic diseases. In modern concepts of pathogenesis of the inflammatory and inflammatory-dystrophic periodontal diseases much attention is paid to the vegetative-vascular disorders. It is known that affection of cervical intervertebral discs is accompanied by affection of the vegetative nervous system. At present the evaluation of vegetative dysfunction manifestations according to A. Vein and determination of its regulatory mechanisms according to Kerdo and Hildebrant has become widespread. However, the use of these simple, safe and informative methods in the patients with periodontal diseases is not sufficiently covered in the special literature. Objective of this research: to study the state of the vegetative nervous system in case of periodontal diseases in the patients with affected cervical intervertebral discs.